THE INFLUENCE OF TRAINING METHODS AND CONCENTRATION ON THE ABILITY TO ROW DISTANCE OF 1000 METERS - Mariana Ditboya Hukubun (Faculty of Teacher Training and Educational Sciences, Pattimura University Indonesia, 2020)
This study were aimed to analyze: (1) the difference influence of interval and fartlek training method toward the result ability of Kayak paddle at the distance of 1000 meter, (2) interaction between training and concentration method toward the ability of paddle at the distance of 1000 meter, and (3) difference influence of high concentration trained by interval and fartlek training method toward the result ability of kayak paddle at the distance of 1000 meter, (4) difference influence of low concentration trained by interval and fartlek training method toward the result ability of kayak paddle at the distance of 1000 meter. This experiment research used 2 x 2 treatment design. The subjects in this study were Kayak paddle athletes of Maluku Province which concsist of 42 people. The techniques of data analysis used was ANAVA. Based on the hypothesis test, the results of this study are: (1) overall there are significant differences between the interval training method and the fartlek training method on the results of the ability to row 1000 meters in rowing athletes like Maluku. , (2) there is an interaction between the training methods used with concentration on the results of the ability to row 1000 meters in rowing athletes like Maluku. Conclusions: (1) interval training method is better than fartlek training method on the ability to row 1000 meters distance, (2) athletes with high concentration and trained with interval and fartlek training methods are better compared with low concentration athletes who are trained with interval training methods and fartlek